2013
DOI: 10.3851/imp2630
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Toll-Like Receptor 3 Expression in Chronic Hepatitis B Patients and Its Restoration by Interferon Therapy

Abstract: CHB patients have reduced TLR3 expression on PBMCs, independent of age, gender and ALT, and on liver cells. Patients with pegylated-interferon-induced SVR have a more significant restoration of TLR3 expression than those under entecavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
5
39
2
Order By: Relevance
“…However, pegylated-IFN or entecavir treatment may induce a sustained virological response that is correlated with a restoration of TLR3 and TLR9 expression. 9,81 In the WHVinfected woodchuck model, we also found that TLR2 expression in PBMCs was negatively correlated with WHV viral loads during acute WHV infection, and increased if WHV loads were suppressed in woodchucks by antiviral treatment. 12 However, these studies did not address the question of whether the functionality of TLRs was also restored by antiviral treatment.…”
Section: Using Tlr Agonists For Immunotherapy In Chronic Hbv Infectionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, pegylated-IFN or entecavir treatment may induce a sustained virological response that is correlated with a restoration of TLR3 and TLR9 expression. 9,81 In the WHVinfected woodchuck model, we also found that TLR2 expression in PBMCs was negatively correlated with WHV viral loads during acute WHV infection, and increased if WHV loads were suppressed in woodchucks by antiviral treatment. 12 However, these studies did not address the question of whether the functionality of TLRs was also restored by antiviral treatment.…”
Section: Using Tlr Agonists For Immunotherapy In Chronic Hbv Infectionmentioning
confidence: 62%
“…However, recent studies have suggested that antiviral treatment in chronic HBV patients can restore the expression of TLRs in PBMCs. 9,12,81 Huang et al demonstrated that chronic HBV patients had lower TLR3 and TLR9 mean fluorescence intensities on PBMCs, liver Kupffer cells and hepatocytes. Hepatic TLR3 and TLR9 mRNA were also significantly reduced in patients.…”
Section: Using Tlr Agonists For Immunotherapy In Chronic Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Human KCs have been proven to express TLR 2-4, while expression of TLR1-9 and retinoic-acid-inducible geneI(RIG-I) have been detected in KCs from rats and mice. 9,10 KCs also express mannose receptors and CD14. 3 The detailed mechanisms of the interaction between KC receptors and HBV/HCV viral protein still remain to be elucidated.…”
Section: Kc Receptors Activated During Hbv/hcv Infectionmentioning
confidence: 99%
“…After the antiviral theraby, the level of TLR3 can be promoted and almost restored. 23 HBV/HCV may influence the produce of immuneregulation cells and improve the tolerance of immune activities. In some study of mouse, it's suggested that the HCV core protein would cuase the higher product of IL-10, and IL-10 could help with immunity tolerance.…”
Section: Kcs Regulate the Immune In Hbv / Hcv Infectionmentioning
confidence: 99%